Mathematics Anxiety in College Students in Costa Rica and their Relatonship with Academic Achievement and Socio-Demographic Variables - Delgado Monge, Islande C. (2017)
The study tried to determine the relationship between mathematics anxiety and the variables of gender, academic achievement, number of times students have taken the course and type of school in students taking the course MAT-001 General Mathematics of the National University of Costa Rica. To that end, a purposive sample of 472 students of such course was collected and the instrument of Hopko, Mahadevan, Bare and Hunt was adjusted to it (2003). Data collected were analyzed with the statistical program SPSS applying the corresponding hypothesis tests. According with the results, students showed a medium level of math anxiety and women showed a math anxiety significantly higher than men, while student graduated from private schools showed a significantly lower level of math anxiety than those from public schools or from the modality “General Equivalency Diploma”. Besides, the higher the math anxiety of the student is, the lower their academic achievement will be. Finally, there were no statistically significant differences between math anxiety and the number of times students have taken the course.